Multilayered Framework to Enhance Management Information Systems Decision on Sensitive Data in Cloud Computing Environment - Haifaa Jassim Muhasin; Rodziah Atan; Marzanah A.Jabar; Salfarina Abdullah; Shahreen Kasim (JOIV : International Journal on Informatics Visualization, 2017)
The purpose of this research is defining the main factors influencing on decision of management system on sensitive data in cloud. The framework is proposed to enhance management information systems decision on sensitive information in cloud environment. The structured interview with several security experts working on cloud computing security to investigate the main objective of framework and suitability of instrument, a pilot study conducts to test the instrument. The validity and reliability test results expose that study can be expanded and lead to final framework validation. This framework using multilevel related to Authorization, Authentication, Classification and identity anonymity, and save and verify, to enhance management information system decision on sensitive data in cloud.